Robust gain scheduled control of spacecraft rendezvous system subject to input saturation - Wang, Qian; Zhou, Bin; Duan, Guang-Ren (Chinese Control Conference, 2014)
The problem of robust control of spacecraft circular orbit rendezvous system subject to input saturation is studied in this paper. The relative model with parameter uncertainties caused by linearization error and saturation nonlinearity is established based on C-W equation. By combining the parametric Riccati equation and the existing gain scheduling technique, a new robust gain scheduling controller is proposed to solve the robust control problem. By scheduling the design parameters online, the convergence rate of the state can be improved. With the designed controller, the spacecraft orbit rendezvous is accomplished successfully. Numerical simulations show the effectiveness of the proposed approach.